Communication and Knowledge Sharing in Multicultural Design Teams - Winkler, Renata; Chmielecki, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The purpose of this article is to analyse the process of knowledge sharing in a multicultural project team and to present aspects of communication to improve its effectiveness. We have conducted a qualitative research study involving 14 managers from nine international companies operating in the finance, outsourcing and IT sectors. The study was designed to isolate key areas of communication and its impact on knowledge sharing in project teams.